2021
DOI: 10.1097/aog.0000000000004607
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcomes Associated With the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Delta (B.1.617.2) Variant

Abstract: Financial Disclosure Rachel G. Sinkey reports money was paid to her institution from GestVision and ProLab. Alan T. Tita reports money was paid to his institution from the NIH, CDC, and Pfizer for COVID-19 and RSV vaccine in pregnancy studies. Ashley N. Battarbee reports money was paid to her institution from the NIH and CDC for COVID-19 in pregnancy studies. Akila Subramaniam reports money was paid to her institution from the NIH. Jeff M. Szychowski reports money was paid to his institution from the NIH. Jodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 1 publication
6
32
2
3
Order By: Relevance
“…The mentioned study reported that cases diagnosed after the spread of the Delta variant were more symptomatic and their gestational age at diagnosis was earlier [ 16 ]. Similarly, a single-center retrospective cohort study from another tertiary center from the United States compared the outcomes of pregnant women diagnosed in the pre-Delta variant period with those diagnosed in the Delta period indicating increased rates of critical illness and adverse perinatal outcomes [ 17 ]. A multicenter prospective cohort study from the United States including 1515 pregnant women reported increased COVID-19-related morbidity after the predomination of the Delta variant especially in populations with lower vaccine acceptance [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned study reported that cases diagnosed after the spread of the Delta variant were more symptomatic and their gestational age at diagnosis was earlier [ 16 ]. Similarly, a single-center retrospective cohort study from another tertiary center from the United States compared the outcomes of pregnant women diagnosed in the pre-Delta variant period with those diagnosed in the Delta period indicating increased rates of critical illness and adverse perinatal outcomes [ 17 ]. A multicenter prospective cohort study from the United States including 1515 pregnant women reported increased COVID-19-related morbidity after the predomination of the Delta variant especially in populations with lower vaccine acceptance [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutations in Delta strains reported may differ depending on the resources consulted [77,93,185]. The description of mutations that occurred in the ORF1ab locus is especially unclear for the Delta variant, and often they do not match from one source to another (Table 2).…”
Section: Beta (B1351 Lineage)mentioning
confidence: 99%
“…Similar reports have also surfaced: The University of Alabama at Birmingham hospital observed an increase in ICU admission from 8% to 29% between the non-Delta and Delta cohorts, as well as an increase in the rates of cesarean delivery preterm birth and NICU admission. All patients admitted to the hospital were unvaccinated [ 2 ].…”
Section: Delta (B16172) and Other Variant Considerationsmentioning
confidence: 99%
“…Ever since the lockdown of Wuhan on 23 February 2020 and the announcement of the global pandemic in March of 2020, the novel coronavirus has claimed over 5 million lives with over 245 million cases [ 1 ], and has greatly impacted every individual around the world in all facets of life, not just physically, but also in terms of economic and social effects that may reverberate through generations to come. This enveloped single-stranded RNA virus from the Coronaviridae family, named the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) [ 2 ], has been greatly researched and reported over the past year, with more and more focus on its impact on each subset of the population. One particular cohort that is in need of further discussion, and which is unfortunately often excluded from trials, is the pregnant population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation